Strategi Untuk Meningkatkan Investor Saham Bermodal Sampah : Studi Di Galeri Investasi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Ampel Surabaya - Anna Putri Syafitri (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2019)
As SALAM Product Promotion Strategy at the Islamic Investment Gallery Faculty of Economics and Islamic Business UIN Sunan Ampel Surabaya is advertising, direct marketing, internet marketing, public relations and publications/public relations, sales promotion and direct sales. Meanwhile, Efforts to Make Students as Trash Capital Investors in the As SALAM Product Promotion Strategy at the Islamic Investment Gallery of the Faculty of Economics and Islamic Business UIN Sunan Ampel Surabaya are collaborating in expanding networks and planning promotional strategies for As SALAM going forward. And efforts to develop and maintain As SALAM products with a defensive strategy, a develop strategy and an intensive strategy, these three strategies are selected in order to realize the objectives of the promotion that has been carried out, after that carry out the promotion strategy in accordance with the promotional mix elements .